100 years of inherited metabolic disorders in Austria—A national registry of minimal birth prevalence, diagnosis, and clinical outcome of inborn errors of metabolism in Austria between 1921 and 2021. Issue 2 (17th October 2021) - Ramoser, Gabriele; Caferri, Federica; Radlinger, Bernhard; Brunner‐Krainz, Michaela; Herbst, Sybille; Huemer, Martina; Hufgard‐Leitner, Miriam; Kircher, Susanne G.; Konstantopoulou, Vassiliki; Löscher, Wolfgang; Möslinger, Dorothea; Plecko, Barbara; et al.
Abstract: Inherited metabolic disorders (IMDs) are a heterogeneous group of rare disorders characterized by disruption of metabolic pathways. To date, data on incidence and prevalence of IMDs are limited. Taking advantage of a functioning network within the Austrian metabolic group, our registry research aimed to update the data of the "Registry for Inherited Metabolic Disorders" started between 1985 and 1995 with retrospectively retrieved data on patients with IMDs according to the Society for the Study of Inborn Errors of Metabolism International Classification of Diseases 11 (SSIEM ICD11) catalogue. Included in this retrospective register were 2631 patients with an IMD according to the SSIEM ICD11 Classification, who were treated in Austria. Thus, a prevalence of 1.8/10 000 for 2020 and a median minimal birth prevalence of 16.9/100 000 (range 0.7/100 000‐113/100 000) were calculated for the period 1921 to February 2021. We detected a male predominance (m:f = 1.2:1) and a mean age of currently alive patients of 17.6 years (range 5.16 months‐100 years). Most common diagnoses were phenylketonuria (17.7%), classical galactosaemia (6.6%), and biotinidase deficiency (4.2%). The most common diagnosis categories were disorders of amino acid and peptide metabolism (819/2631; 31.1%), disorders of energy metabolism (396/2631; 15.1%), and lysosomal disorders (395/2631; 15.0%). In addition to its epidemiological relevance, the "Registry for Inherited Metabolic Disorders" is an important tool for enhancing an exchange between care providers. Moreover, by pooling expertise it prospectively improves patient treatment, similar to pediatric oncology protocols. A substantial requirement for ful filling this goal is to regularly update the registry and provide nationwide coverage with inclusion of all medical specialties.